Фольклор Поділля - одне із джерел повісті Тараса Шевченка "Варнак": інтерпретація мотивів та образів - Шалак, Оксана; Shalak, Оksana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Дослідниця осмислює зв’язок повісті Т. Шевченка «Варнак» із фольклорними переказами, легендами, піснями, розглядає спільні мотиви та концепти, інтерпретаційні засоби, до яких вдавався письменник. Завдяки порівняльному аналізу О. Шалак виявляє основні джерела повісті «Варнак», досліджує розвиток світоглядних та художніх засад Т. Шевченка. The researcher comprehends the relationship of story of T. Shevchenko «Varnak» with folk traditions, legends, songs, investigates (treats) common motifs and concepts, interpretive means, resorted to by the writer. Due to the comparative analysis, the author identifies the main sources of the story «Varnak», explores the development of philosophical and artistic principles T. Shevchenko. The researcher refers to the biographic facts, to the epistolary heritage, with deep arguments proves that the poet knew songs, legends about Karmaljuke occurring on Podolii. He creatively used separate plots and characters under writing «Varnak». Main concepts general for folklore and story are analysed. It’s the repentant robber, the fair avenger, disguise, renaming, forest shelter, a fire, shackles. T. Shevchenko has reconsidered the image of shackles, gave it the meaning of repentance at own and others sins.
Folklore of Podillya as sources of story by Taras Shevchenko «Varnak»: interpretation of motifs and characters
Keywords: Тарас Шевченко; повість «Варнак»; Устим Кармалюк; мотив; концепт; Taras Shevchenko; story «Varnak»; Ustym Karmalyuk; the motif; the concept